Analysis of the actual directions of the management of national productivity - Berveno, Oksana; Moskvina, Anastasiya (Technology audit and production reserves, 2017)
The important factor that determines the national economic development is the national productivity that determines institutional structure of national economy and limits or widens its possibilities to react on new challenges. The productivity of national economy is a cornerstone that the long-term stable economic development cannot be attained without. The aim of the article is to analyze the priority factors of the national productivity formation and the search for the ways of influencing it by the state and society. The growth of national productivity needs the proportionate complementarity of social and economic components of national development that becomes mainly the result of not economic changes but social ones. Social context, gaining more and more influence on national productivity, determines also the urgent directions of national management. The management of national productivity is based on the formation of stable socio-economic relations. In modern conditions the effectiveness of socio-economic relations depends on human factor and synchronously influences its development. The elements of socio-labor relations that play the important role in national productivity formation are the main parameters of labor life: conditions and content of labor, organization of labor activity, labor payment, labor guarantees, labor prestige, motives and stimuli. Within labor activity takes place the widening of social connections, increase of self-appraisal at the expanse of feeling of own contribution in common matter. The combination of economic and social effectiveness of labor is the important factor of long-term positive trend of national productivity. More productive economy can support a higher wage and higher profit and also widening of free time and higher life quality. The modern socio-labor policy must be built based on understanding of the priority role of human, its creative abilities in social reproduction. The management of national productivity must be of system character that provides transformation of the results of previous economic development in stable future development. The important aspects of the national productivity management include the support of the quality of socio-labor sphere development, conditions of realization of main competitive advantage of the country – high-educated and creative working force. The management of national productivity must have close connections with other directions of state policy, especially innovative, educational, social and so on.